(untitled) (Iranian Journal of Kidney Diseases, 2016)
Introduction. Hypertension is a worldwide health concern. Complications of hypertension not only affect adult patients, but also involve children. Given the importance of assessing children with hypertension in order to decrease adulthood complications, we aimed to assess the prevalence of hypertension in urban school-aged children in Rasht, Iran. Materials and Methods. This cross-sectional study was conducted on 2072 school-aged children in Rasht, Iran, from January 2013 to December 2015. Inclusion criteria were age between 7 and 17 years and residence and attending school in the urban area of Rasht. Results. Overall, 205 (9.9%) and 144 (6.9%) of the participants were hypertensive and prehypertensive, respectively. The mean systolic blood pressure was 124.54 ± 11.86 mm Hg in the children. The prevalence of obesity in the children was 3.5%. Comparing the normal, prehypertensive, and hypertensive groups, there was a significantly increasing trend regarding age, height, weight, and body mass index associated with higher blood pressure categories. Conclusions. This study showed a high rate of hypertension among school-aged children in Rasht. Hypertensive children tended to be have a higher body mass index than the prehypertensive and normal-weight participants. Case identification and early assessment of these children is recommended.